Analisis Pendapatan Pajak Kendaraan Bermotor Dan Persepsi Wajib Pajak Sesudah Diberlakukannya Insentif PKB Selama Pandemi Pada Dinas Pendapatan Daerah Kota Bangli - Widiantari, Ni Komang Ayu Indah; Sulindawati, Ni Luh Gede Erni (Universitas Pendidikan Ganesha, 2022)
The Covid-19 pandemic in 2020 had a major impact on the economy. The impact that occurs in almost all sectors, on of which is the tax sector. As a result of this impact, many policies were made by the government to deal with the impacts that occurred during the Covid 19 pandemic in 2020. One of the government’s policies in responding to the impact oh the Covid 19 pandemic is the tax incentive policy on Motor Vehicle Taxes. Local government policies are in the form of socialization activities through print and non-print media, mobile tax services via the Samsat Bus, payments via e-samsat at Bank Bangli ATMs. The results of the study indicate that the provision of Motor Vehicle taxpayers in paying taxes owed so as income, perception, incentive, regional income to increase revenue